The effect of the COVID-19 pandemic on TVET providers and programmes in Ghana - Asamoah, Fred Kyei [Verfasser] (My University, 2022)
„The Commission for TVET has the mandate to steer the TVET transformation in Ghana and regulate, promote, and administer technical and Vocational Education and Training for transformation and innovation for sustainable development in the country. In light of the COVID-19 pandemic, TVET training providers (TP) were confronted with enormous challenges due to school closures and disruption of the academic calendar. The switch to virtual formats was pursued by most TPs but challenged due to high costs of Internet or the limited availability of stable connections.“ (author’s abstract; BIBB-Doku)
Keywords: I 2.3.1 Afrika; 370; Berufsausbildung; Anbieter; Pandemie; Auswirkung; Ghana